Using voltage signals for transient fault detection on overhead lines. (May 2022) - Belčević, Nenad M.; Stojanović, Zoran N.
Highlights: Transient faults on overhead lines are followed by an electric arc. Autoreclosure technique exposes the equipment to stress in case of permanent faults. Saturation of the current transformer leads to current distortion on its secondary. Saturation of the current transformer can prevent the detection of an electric arc. The use of voltage signals allows arc detection regardless current signal deformity. Abstract: A basic feature of transient faults on overhead lines is the occurrence of an electric arc at fault location. Short-term de-energisation of the overhead line enables the termination of electric arcing, which has led to the widespread application of the autoreclosure technique. The greatest shortcoming of this technique is its indiscriminate application regardless of fault type. This paper presents a novel approach to fault type identification on overhead lines, based on primary electric arc voltage estimation. The information on fault type blocks the autoreclosure system in case of a metallic (permanent) fault. The key advantage of the presented algorithm is the fact that it is based on voltage signal processing exclusively, which allows for its reliable operation under current transformer saturation too. The conducted tests have affirmed the algorithm's high reliability and robustness.